Ethical community, civil society and market sketches for a critique of the neoliberal revolution from the Kantian concept of ethical community - Caviglia, Alessandro (2017)
The present work takes on the Kantian concept of ethical community as a critical starting point to construct a conception of civil society that can cope with the pretensions of an exaggerated capitalism that has been articulated through the forging of a global self-regulated market. In order to carry out the analysis, classical works in economic anthropology, such as those of Marcel Mauss and Marshal Sahlins, together with Karl Polanyi’s studies on economics, sociology and economics have been taken as additional support and re-evaluated through the perspective of contemporary works on political and social philosophy.